Pemanfaatan Teknologi Augmented Reality sebagai Media Komunikasi Informasi dalam Dunia Bisnis - Maulana, Muhammad Hikam; Suryana, Asep; Koswara, Iwan (UNIVERSITAS SARI MUTIARA INDONESIA, 2024)
This article intends to examine the use of AR technology in the context of its application in the wider business world. Apart from that, the limitations and future research contained in the previous article will also be explained in this article. . This research adopts the systematic literature review (SLR) guidelines proposed by Xiao & Watson (2019) with eight main steps . Therefore, to obtain deeper information, researchers asked several research questions. First, how has the use of Augmented Reality (AR) in a business context been developed and implemented widely, What challenges and opportunities does the use of AR present in the business world, What effectiveness and efficiency results from using AR in business.The importance of enhancing consumer engagement and experience in online shopping drives companies to continuously innovate to create a competitive edge in business. Augmented reality is said to be able to create this advantage in terms of processes and services. This research aims to analyze how the utilization of AR technology in the business world and explain the challenges and opportunities generated from its use. To understand the extent of AR utilization in business, a systematic literature review (SLR) of previous studies published no later than 2014 was conducted. The results of this research indicate that the majority of AR technology utilization in business is to visualize products in 3D in the real world and display virtual product trials. The explanation of challenges and opportunities generated can serve as anticipation and strategies for companies to advance their business sustainability.